2013
DOI: 10.1200/jop.2013.000929
|View full text |Cite
|
Sign up to set email alerts
|

Cost Concerns of Patients With Cancer

Abstract: Purpose: Health care providers are accustomed to identifying populations for whom cost-related concerns may be a significant barrier, such as the poor, but few empiric data have been collected to substantiate such assumptions, particularly among insured patients. Methods:Patients with cancer from academic and community hospitals completed a questionnaire that included closedended items concerning demographic variables, optimism, numeracy, and concerns about present and future medical costs. In addition, they a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 16 publications
2
55
0
Order By: Relevance
“…Out-of-pocket costs and financial concerns may be substantial even when the survivors have health insurance coverage [9, 1921]. Across diverse studies, more than one third of survivors report concerns paying for medical care, financial hardship, or having had financial problems related to cancer [19, 21, 22]. Moreover, concerns are not unique to survivors in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Out-of-pocket costs and financial concerns may be substantial even when the survivors have health insurance coverage [9, 1921]. Across diverse studies, more than one third of survivors report concerns paying for medical care, financial hardship, or having had financial problems related to cancer [19, 21, 22]. Moreover, concerns are not unique to survivors in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…This means that the cost of treatment can become a major factor in decision making for cancer patients. 10 Many patients will forego high-cost treatments altogether, or discontinue them early if the expense becomes prohibitive. 11 A recent survey of medical oncologists from the USA indicated that the vast majority felt obliged to offer all available treatment options to their patients regardless of their cost.…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…8 Conversely, patients who are appropriately enrolled in hospice care report better symptom management and have a greater likelihood of dying in their preferred place 9 and with lower overall costs. 17 By 2015, close to one-half of Medicare decedents received hospice services. 13,14 Place of death last was examined comprehensively in 2004, when simple trend data from 1980 through 1998 demonstrated a decrease in hospital deaths and an increase in home deaths, the majority noted among the population of patients with cancer.…”
Section: Introductionmentioning
confidence: 99%